2020
DOI: 10.3174/ajnr.a6585
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal MRI Predictors of Aggressive Early Clinical Course in Vein of Galen Malformation

Abstract: BACKGROUND AND PURPOSE: Neonates with vein of Galen malformations are split into 2 cohorts: one needing urgent neonatal embolization, with relatively high mortality and morbidity even with expert care, and a cohort in which embolization can be deferred until infancy, with far better prognosis. We aimed to identify brain MR imaging characteristics obtained from fetal and early neonatal scans that can predict the clinical presentation. MATERIALS AND METHODS:Patients with vein of Galen malformations were stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…For the secondary outcome of efficacy, fetuses with VOGMs measuring>8 mm in the straight sinus or falcine sinus historically have 88% likelihood of requiring neonatal intervention. 14 Using a conservative estimate of 80% requiring such intervention, with a goal of 50% absolute reduction in the need for neonatal intervention to a rate of 30%, the proposed 20-patient cohort would have 80% power to demonstrate statistically significant efficacy of the study intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the secondary outcome of efficacy, fetuses with VOGMs measuring>8 mm in the straight sinus or falcine sinus historically have 88% likelihood of requiring neonatal intervention. 14 Using a conservative estimate of 80% requiring such intervention, with a goal of 50% absolute reduction in the need for neonatal intervention to a rate of 30%, the proposed 20-patient cohort would have 80% power to demonstrate statistically significant efficacy of the study intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A subset analysis suggested that volume over 40 mL may also be at increased risk of late gestational progression. With a larger cohort from the USA and a systematic review of multiple intracranial vascular measurements on fetal MRI, the mediolateral width of the straight or falcine sinus at its point of tightest constriction was found to most robustly correlate with neonatal decompensation necessitating endovascular intervention, more than any other measured vascular parameter, that is, this variable reliably predicted eventual presentation of the fetus in the NAR cohort after delivery 14. This particular parameter is consistent with physiological intuition, as the point of tightest constriction of the venous sinus draining the prosencephalic varix is a definitive limiting point on overall flow return from the malformation to the systemic circulation.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…During weeks 6 to 11 in utero, the median prosencephalic vein is responsible for venous drainage from the developing fetal choroid plexus. As the typical embryological course continues, the vein of Markowski would eventually regress and the internal cerebral veins would take shape and continue drainage of the growing choroid plexus [ 3 ]. However, in the case of the congenital vein of Galen malformation, an arteriovenous shunt develops within the median prosencephalic vein instead.…”
Section: Discussionmentioning
confidence: 99%
“…Infrequently, during weeks 6-11 of fetal development in utero, an abnormality can occur within the median prosencephalic vein, and an arteriovenous shunt instead arises, which is called the vein of Galen malformation [ 3 ]. The shunt allows for more blood to flow into this vein causing its dilation.…”
Section: Introductionmentioning
confidence: 99%